Essential Oil Nanoemulsion as Eco-Friendly and Safe Preservative: Bioefficacy Against Microbial Food Deterioration and Toxin Secretion, Mode of Action, and Future Opportunities - Maurya, Akash; Singh, Vipin Kumar; Das, Somenath; Prasad, Jitendra; Kedia, Akash; Upadhyay, Neha; Dubey, Nawal Kishore; Dwivedy, Abhishek Kumar (Frontiers in Microbiology, 2021)
Microbes are the biggest shareholder for quantitative and qualitative deterioration of food commodities at different stages of production, transportation, and storage along with the secretion of toxic secondary metabolites. Indiscriminate application of synthetic preservatives may develop the resistance microbial strains and associated complications in human health with broad spectrum environmental non-sustainability. Application of essential oils (EOs) as natural antimicrobial and its efficacy for preservation of foods has been a crescent interest and growing consumer demand in the current generation. However, loss in bioactivity of EO by fluctuating environmental conditions is the major limitation during practical application, which could be overcome by encapsulating them in suitable biodegradable and biocompatible polymer matrix with enhancement in their efficacy and stability. Among different nanoencapsulated systems, nanoemulsions effectively contribute practical applications of EOs by expanding their dispersibility and foster their controlled delivery in food system. In line with the above background, this review aims to present enabling practical application of nanoemulsions a) by addressing their direct and indirect (EO nanoemulsion coating leading to active packaging) consistent support in real food system, b) biochemical actions related to antimicrobial mechanisms, c) effectiveness of nanoemulsion as bio-nanosensor with large scale practical applicability d) critical evaluation of toxicity, safety and regulatory issues and e) market demand of nanoemulsion in pharmaceuticals and nutraceuticals along with the current challenges and future opportunities.